Analisis Perbandingan (ECAP) Antara Material Aluminium-Silikon dan Silikon Karbida untuk Pelapisan Komponen Tahan Abrasi - Aydin, Muhammad Syabil; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2026)
Aluminum-silicon alloy and silicon carbide (SiC) are materials known for their high thermal resistance and mechanical strength; however, their brittleness limits their use in mechanical structures, particularly for coating components that require abrasion resistance. Equal Channel Angular Pressing (ECAP), commonly applied to metals, is a plastic deformation technique with the potential to enhance the mechanical properties of brittle materials. While ECAP has proven effective in improving the hardness and microstructure of metals, its application to ceramic materials like SiC remains underexplored, especially for abrasion-resistant coatings. This study aims to analyze and compare the effects of ECAP on the hardness and microstructure of aluminum-silicon alloy and SiC annealed at 300°C, to evaluate their potential as abrasion-resistant coatings. The research methodology includes sample heating to 300°C, ECAP processing with a 120° die, Brinell hardness testing, and microstructure analysis using electron microscopy. The results of this study are expected to provide insight into the effectiveness of ECAP in enhancing the mechanical performance of these materials, expanding their potential for applications in abrasion-resistant coatings.